2011
DOI: 10.1016/j.jpsychires.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of emotional processing in depression: Changes with cognitive behavioral therapy and predictors of treatment response

Abstract: a b s t r a c tMajor depressive disorder (MDD) is characterized by the presence of disturbances in emotional processing. However, the neural correlates of these alterations, and how they may be affected by therapeutic interventions, remain unclear. The present study addressed these issues in a preliminary investigation using functional magnetic resonance imaging (fMRI) to examine neural responses to positive, negative, and neutral pictures in unmedicated MDD patients (N ¼ 22) versus controls (N ¼ 14). After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
201
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(224 citation statements)
references
References 70 publications
8
201
2
3
Order By: Relevance
“…Two fMRI studies reported post-CBT increases in superior frontal gyrus/DMPFC (BA8) activity when processing emotional stimuli, though Yoshimura et al found it increased on judging whether positive emotional trait words applied to them and Fu et al increased on processing sad facial expressions (23,28 (23,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Two fMRI studies reported post-CBT increases in superior frontal gyrus/DMPFC (BA8) activity when processing emotional stimuli, though Yoshimura et al found it increased on judging whether positive emotional trait words applied to them and Fu et al increased on processing sad facial expressions (23,28 (23,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…"The imaging data have been really encouraging, " says Timothy Strauman, a psychologist at Duke University in Durham, North Carolina, who has generated similar results 7 . "We do find evidence for the kinds of changes that you would expect.…”
Section: Unravelling Mechanismsmentioning
confidence: 93%
“…However, it is currently unclear which patients will show a favorable or unfavorable course. Studies on treatment response have indicated the importance of structure and functioning of the lateral prefrontal cortex (PFC) (Heller et al, 2013;Langenecker et al, 2007;Ritchey et al, 2011), medial PFC (Ritchey et al, 2011), anterior cingulate cortex (ACC) (Fu et al, 2013;Kemp et al, 2008;Pizzagalli, 2010), insula (Fu et al, 2013;Langenecker et al, 2007;McGrath et al, 2013), amygdala (Langenecker et al, 2007), and hippocampus (Frodl et al, 2004;Fu et al, 2013) for predicting remission following treatment. However, treatment-response markers are not necessarily markers of a naturalistic course of depression.…”
Section: Introductionmentioning
confidence: 99%